Antidepressant use during pregnancy and risk of postpartum hemorrhage: A systematic review and meta-analysis. (December 2016) - Jiang, Hai-yin; Xu, Lian-lian; Li, Yu-cuan; Deng, Min; Peng, Chun-ting; Ruan, Bing
Abstract: Evidence about relationship between antidepressant use during pregnancy and the risk of postpartum hemorrhage (PPH) is conflicting. The aim of this meta-analysis was to systematically assess this relationship. To identify relevant studies, we conducted systematic searches in PubMed and Embase of articles published through May 2016. Random-effects models were adopted to estimate overall relative risk. In total, eight studies involving more than 40, 000 PPH cases were included in our meta-analysis. After pooling the estimates, the odds for developing PPH were 1.32-fold higher (risk ratio, RR = 1.32; 95% confidence interval, CI = 1.17–1.48) in antidepressant users compared with individuals who had not taken antidepressants. In subgroup analyses, the associations still exist for women with exposure to non-SRI (RR = 1.31, 95% CI = 1.1–1.56), SRIs (RR = 1.23, 95% CI = 1.06–1.44), SSRIs (RR = 1.2, 95% CI = 1.04–1.38), and SNRIs (RR = 1.62, 95% CI = 1.41–1.85). Based on exposure window, we found an increased risk of PPH among current (RR = 1.37, 95% CI = 1.09–1.71) and recent users (RR = 1.32, 95% CI = 1.15–1.51), but not past users (RR = 1.08, 95% CI = 0.88–1.31). The findings of this meta-analysis support an increased risk of PPH in women exposure to antidepressant during late gestation.